2008
DOI: 10.1002/cncr.23283
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonectomy after chemoradiation

Abstract: Acute lymphoblastic leukemia (ALL) is the most common cancer in children. The current treatment protocol for ALL involves an intense chemotherapy regimen yielding cure rates of nearly 80%. However, new therapies need to be designed not only to increase the survival rate but also to combat the risk of severe therapy associated toxicities including secondary malignancies, growth problems, organ damage, and infertility. The c‐Myb proto‐oncogene is highly expressed in immature hematopoietic cells. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Nonetheless, when exploring the long term benefits of the NA therapy the survival rate, was found to be 30% eight years post-OP, significantly higher than the adjuvant group that was 0% at 5.5 years post-op [10]. The long-term outcomes of the pneumonectomy + adjuvant treatment group observed in our cohort are in concordance with the historically poor outcomes of single-modality therapy in stage IIIa NSCLC patients [1012].…”
Section: Discussionsupporting
confidence: 73%
“…Nonetheless, when exploring the long term benefits of the NA therapy the survival rate, was found to be 30% eight years post-OP, significantly higher than the adjuvant group that was 0% at 5.5 years post-op [10]. The long-term outcomes of the pneumonectomy + adjuvant treatment group observed in our cohort are in concordance with the historically poor outcomes of single-modality therapy in stage IIIa NSCLC patients [1012].…”
Section: Discussionsupporting
confidence: 73%
“…Right pneumonectomy following neoadjuvant therapy has been associated with significantly increased mortality risk, regardless of addition of novel systemic agents. For example, there has been a reported 18% treatment-related mortality rate after right pneumonectomy, compared to a 4% rate after left pneumonectomy, after neoadjuvant radiotherapy to a median dose of 54 Gy with concurrent chemotherapy [46].…”
Section: Discussionmentioning
confidence: 99%
“…The main reason was the morbidity and mortality rates of pneumonectomy (26% mortality), especially right pneumonectomy. Since the publication of INT 0139 a number of studies have shown that in experienced hands the mortality rate of pneumonectomy is unchanged following chemoradiation [18, 19]. Moreover, a number of trials have been published showing a lack of clear survival benefit for chemoradiation over induction chemotherapy followed by surgery [20-22].…”
Section: Discussionmentioning
confidence: 99%
“…Since the publication of the results of the intergroup trial multiple investigators have shown that in experienced hands pneumonectomy following chemoradiation is indeed safe even with increased doses of preoperative radiation therapy [3, 4]. The question that can then be asked is: would increased-intensity preoperative chemoradiation lead to improved nodal downstaging and thereby improved long-term survival?…”
Section: Introductionmentioning
confidence: 99%